Mutation in Honeybees 2. Average Rate of Mutation Based on Seven Genes for Eye Colour - Chaud-Netto, José [UNESP]; Kerr, Warwick Estevam; Bezerra, Marcela A. F. (Taylor & Francis, 1983)
The average numbers of ommatidia in the eyes of workers was 3826 and in the eyes of males 7082. Somatic mutations from recessive to dominant were detected in 7 genes, some reported in this paper, some in an earlier publication. The rates of reverse mutation estimated for males were: for chr, µ=3 38 × 10−6; for oc, µ=l 96 × 10−6; for pe, µ=0 17 × 10−6, for sla, µ=1 10 × 10−6 and for sp, µ=2 17 × 10−6. The average was µ=l 75 × 10−6 or, without pe, µ=2 15 × 10−6. Estimates for workers were: for by, µ=0 67 × 10−6; for chr, µ=l 45 × 10−6; for chli, µ=l 39 × 10−6; for oc, µ=l 56 × 10−6; for sla, µ = 0 25 × 10−6; for sp, µ=l 53 × 10−6. The average for workers was µ=1 14 × 10−6 or, without sla, µ=1 32 × 10−6. The balanced average somatic mutation rate for drones and workers was µ= 1 6 × 10−6. So far, cr has not shown a single case of reverse mutation, which indicates that either its rate of mutation is less than 2 0 × 10−8 or that it results from a chromosomal deletion. In all cases the mutation rate for a particular gene was greater in males than in workers. © 1983 International Bee Research Association.